The Effect Of Duration Time On Onggok Fermentation With Enrichment N, S, P By Trichoderma Reesei On Nutrien Value - Nila Cahyaning Febriyani; Agung Subrata; Surahmanto Surahmanto; Joelal Achmadi (LPPM Perjuangan University of Tasikmalaya, 2020)
The aim of this research was to study the effect of incubation time on onggok fermentation with enrichment N, S, P by Trichoderma reesei on nutrient value. The materials of this research were onggok, T. Reesei and N, S, P element. This research used completely randomized design with 4 treatments different incubation time with 5 replication; T0: 0 day, T1: 2 days, T2: 4 days and T3: 6 days. The parameters observed were crude protein, crude fat, crude fiber, and nitrogen free extract of fermented onggok. Data analysis was used by Analysis of Variance (ANOVA) and continued by Duncan’s Multiple Range test if they were significantly different. Results of this research showed that there were haven’t effect (P>0.05) of the treatment on nutrient value. The conclusion of this research was incubation time on onggok fermentation with enrichment N, S, P by Trichoderma reesei have not been able to decrease crude fiber.Keywords : Onggok, fermentation, T.reesei